1990
DOI: 10.1111/j.1365-2133.1990.tb01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to irritants: role of barrier function, skin dryness and history of atopic dermatitis

Abstract: The susceptibility of the skin to various irritants was investigated with the aim of determining the role of the barrier function of the stratum corneum, skin dryness and whether a history of atopic dermatitis (AD) was a factor. The transepidermal water loss (TEWL) was measured using an evaporimeter and skin hydration using a Corneometer and by visual scoring. The group with a history of AD (n = 20) had a lower pre-exposure barrier function and a higher TEWL value following irritant exposure than the group wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
1
3

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(105 citation statements)
references
References 20 publications
10
91
1
3
Order By: Relevance
“…An experimental stud y demonstrated that individuals with dry skin react more strongly to exposure to irritants (9). Other studies found that dry skin was a risk factor, particularly in combination with atopic dermatitis (27) or with atopic mucosal symptoms (28) .…”
Section: Discussionmentioning
confidence: 99%
“…An experimental stud y demonstrated that individuals with dry skin react more strongly to exposure to irritants (9). Other studies found that dry skin was a risk factor, particularly in combination with atopic dermatitis (27) or with atopic mucosal symptoms (28) .…”
Section: Discussionmentioning
confidence: 99%
“…here is a general consensus that disruption of the barrier function of the stratum corneum is an essential etiologic factor for skin inflammation in patients with atopic dermatitis (AD) (Gloor et al, 1981;Ogawa and Yoshiike, 1993;Tupker et al, 1990). Dysfunction of the stratum corneum seems to be associated with the increased permeability and penetration of environmental irritants and allergens in clinically normal AD skin (Cooper, 1994;Deleuran et al, 1998;Fitzharris and Riley, 1999;Gloor et al, 1981;Ogawa and Yoshiike, 1993;Rothe and Grant-Kels, 1996;Tan et al, 1996;Tanaka et al, 1994;Tupker et al, 1990), which predisposes it to inflammation (Broberg et al, 1992;Lammintausta et al, 1993).…”
mentioning
confidence: 99%
“…Basically, a markedly increased transepidermal water loss and a markedly decreased water holding capacity of the stratum corneum were reported in AD patients (Watanabe et al, 1991). In addition, since the patients showed a higher transepidermal water loss following irritant exposure, the susceptibility to irritants in AD patients seemed to be closely related with a breakdown in the barrier function of the stratum corneum (Tupker et al, 1990). More recently, it has been proposed that AD is a multifactorial, heterogenous disease that arises as a result of the interaction between both environmental and genetic factors (Cork et al, 2009).…”
Section: Skin Barrier Dysfunctionmentioning
confidence: 99%